A match made in heaven : American Jews, Christian Zionists, and one man's exploration of the weird and wonderful Judeo-Evangelical alliance /: American Jews, Christian Zionists, and one man's exploration of the weird and wonderful Judeo-Evangelical alliance. (2009) - Unknown
No abstract available